MICROWAVE-ASSISTED, SOLVENT FREE AND PARALLEL SYNTHESIS OF SOME NEWER 2, 4-DISUBSTITUTED 1, 5- BENZODIAZEPINES OF BIOLOGICAL INTEREST (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Benzodiazepines and their derivatives were reported to have wide biological activities and were synthesized by the reaction between substituted benzaldehydes and substituted ketones in presence of sodium hydroxide to afford chalcones and further reaction between 1, 2-diamine under smooth condensation with chalcones in presence of glacial acetic acid afforded a new class of 1, 5-benzodiazepines in good yield. 2, 4-disubstituted 1, 5-benzodiazepine derivatives (1B-19B) were synthesized by microwave and conventional methods. The synthesized compounds were evaluated for their antibacterial, antifungal, anthelmintic and cytotoxic activity. The chemical structures of the newly synthesized compounds have been confirmed by IR, 1H-NMR, MASS spectral data and elemental analysis. All the synthesized substituted benzodiazepines have shown good antimicrobial activity, moderate to good anthelmintic activity and possessed significant cytotoxic activity.